The Mechanism Action of German Chamomile (Matricaria recutita L.) in the Treatment of Eczema: Based on Dose–Effect Weight Coefficient Network Pharmacology - Wang, Wenfei; Wang, Yichun; Zou, Junbo; Jia, Yanzhuo; Wang, Yao; Li, Jia; Wang, Changli; Sun, Jing; Guo, Dongyan; Wang, Fang; Wu, Zhenfeng; Yang, Ming; et al. (Frontiers in Pharmacology, 2021)
To determine the active ingredients in German chamomile volatile oil and the mechanism of action in the treatment of eczema , this study uesd two parameters (ingredient content and oil-water partition coefficient) and established a new network pharmacology method based on dose-effect weight coefficient . Through the new network pharmacology method, we found that German chamomile volatile oil regulated T cell lymphatic subpopulations to inhibit the Th17 cell differentiation signaling pathway. This resulted in a reduction of interleukin 17(IL-17), thereby inhibiting activation of the nuclear factor kappa beta （NF-κB）and MAPK pathways,decreasing the secretion of the pro-inflammatory factors (tumor necrosis factor alpha(TNF-α) and Interleukin 6（IL-6),and reducing inflammation. In this study, a new dose-effect relationship synergistic network pharmacology method was established to provide a new method for the screening of effective ingredients and pathways of drugs, and to provide a basis for follow-up studies of German chamomile volatile oil in the treatment of eczema.